Kashmir Dispute between India and Pakistan: Implication for the Regional Peace and Stability in South Asia (Journal of Interdisciplinary Insights, 2025)
The Jammu and Kashmir dispute remains one of the longest-standing conflicts since the establishment of the United Nations. Since 1947, India and Pakistan have engaged in multiple wars and military standoffs over the contested territory, risking regional and global stability due to their nuclear capabilities. Despite numerous United Nations Security Council (UNSC) and United Nations Commission for India and Pakistan (UNCIP) resolutions advocating for a peaceful settlement through a plebiscite, India’s persistent non-compliance has stymied any resolution efforts. This paper provides an in-depth analysis of the historical background, the complex geopolitical dimensions, and India’s human rights violations in Jammu and Kashmir. It also evaluates recent escalations, particularly the military standoff of 2025, and highlights the critical role of international mediation in averting a catastrophic conflict. The study argues that without a just resolution in line with UN mandates and Kashmiri aspirations for self-determination, South Asia will remain vulnerable to further instability. The study underscores the urgent need for structured dialogue, credible mediation, and strategic restraint by both nuclear-armed neighbors to secure lasting peace in the region.